Influencer Driven Strategies for Regaining Customer Trust and Loyalty in Established Brands - Rahmadi, Didik (Celebes Scholar pg, 2023)
This study looks at the presumption that influencer-driven strategies are efficient in rebuilding purchasers’ trust and devotion for fixed brands. Adopting a dual-process strategy, we tested the influence of authenticity, engagement, and knowledge of influencers on consumers’ responses. Simple analysis showed that there was a huge expansion of ‘agree with’ and loyalty rankings after adopting influencer-driven techniques. These were supported by inferential analyses, which included t-tests, regression, correlation, ANOVA and ANCOVA. The effects revealed that influencers without doubt influence purchaser believe and loyalty, with authenticity as the biggest predictor of accept as true with. Likewise, demographic components were once again observed to understate the efficiency of those strategies. This look at responds to an important gap in the literature by showing the rehabilitative affordance of influencer advertising for a spectrum of purposes beyond pure promotion. The findings given provide specific guidance for the brands that seek to revitalize their reputation and create loyal customer base via competent influencer marketing collaborations.